The path to a hemocompatible cardiovascular implant: Advances and challenges of current endothelialization strategies - Vasileios Exarchos; Vasileios Exarchos; Ema Zacharova; Ema Zacharova; Ema Zacharova; Sebastian Neuber; Sebastian Neuber; Costanza Giampietro; Costanza Giampietro; Sarah E. Motta; Hristian Hinkov; Hristian Hinkov; et al. (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular (CV) implants are still associated with thrombogenicity due to insufficient hemocompatibility. Endothelialization of their luminal surface is a promising strategy to increase their hemocompatibility. In this review, we provide a collection of research studies and review articles aiming to summarize the recent efforts on surface modifications of CV implants, including stents, grafts, valves, and ventricular assist devises. We focus in particular on the implementation of micrometer or nanoscale surface modifications, physical characteristics of known biomaterials (such as wetness and stiffness), and surface morphological features (such as gratings, fibers, pores, and pits). We also review how biomechanical signals originating from the endothelial cell for surface interaction can be directed by topography engineering approaches toward the survival of the endothelium and its long-term adaptation. Finally, we summarize the regulatory and economic challenges that may prevent clinical implementation of endothelialized CV implants.